Energy storage performance and irreversibility analysis of a water-based suspension containing nano-encapsulated phase change materials in a porous staggered cavity. (September 2022) - Hussain, Shafqat; Molana, M.; Armaghani, T.; Rashad, A.M.; Nabwey, Hossam A.
Abstract: This paper reports the methodology and results of a numerical investigation on energy storage performance of a water-based suspension of nano-encapsulated phase change material in a porous staggered cavity. A high order Galerkin finite element method was applied to solve the governing equations. The effects of different parameters like Darcy number, Stafan number, Rayleigh number, Bejan number and thermal conductivity ratio on entropy generation and heat transfer were examined. Results showed that in increase in Darcy number leads to enhance the average heat transfer, entropy generation and kinetic energy. The kinetic energy also grows considerably with any increase in the nanoparticle volume fraction, especially at lower thermal conductivity ratios. Highlights: Energy storage of NEPCM suspended in water inside a very novel shape of porous staggered cavity. Changing the Ra from 10 3 to 10 6, increases the average kinetic energy. Kinetic energy grows with any increase in Stefan number.